Impact of sorghum grain processing on morphological characteristics of particles of wholegrain sorghum flour - Acquisgrana, María del Rosario (2021)
This work studies the physical characteristics of sorghum whole flour particles produced with grains reduced in tannins by hydrothermal treatment. Flours ground with two types of mills: a roll mill and a blade mill were used; grains were hydrated with a moisture content of 25%. For this moisture the maximum yield was obtained. The effect of the grain moisture during the grinding was evaluated regarding the morphological characteristics, the granulometry and fractal dimension (Df) of particles. In all the analysed samples, bimodal size distribution curves were obtained. The treated samples showed medium size particles bigger than the samples without treatment. The samples without hydrothermal treatment presented particles with lower damage than the treated samples for both mills. The difference in Df between samples indicated more roughness for the samples with treatment. The proposed treatment could contribute to the development of sorghum whole flour with different properties for the development of gluten-free food.